2010
DOI: 10.1212/wnl.0b013e3181c7da20
|View full text |Cite
|
Sign up to set email alerts
|

Ictal SPECT statistical parametric mapping in temporal lobe epilepsy surgery

Abstract: Objective: Although subtraction ictal SPECT coregistered to MRI (SISCOM) is clinically useful in epilepsy surgery evaluation, it does not determine whether the ictal-interictal subtraction difference is statistically different from the expected random variation between 2 SPECT studies. We developed a statistical parametric mapping and MRI voxel-based method of analyzing ictalinterictal SPECT difference data (statistical ictal SPECT coregistered to MRI [STATISCOM]) and compared it with SISCOM. Methods:Two seria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 16 publications
1
40
0
3
Order By: Relevance
“…O-15 PET images represent the immediate perfusion state of the brain at the time of image acquisition and are essentially limited to interictal (between seizures) studies because of the logistical challenge of injecting and immediately scanning the patient during a seizure. Cerebral blood flow is an important diagnostic metric in stroke (Liebeskind, 2009), neurodegenerative disease (Josephs et al, 2006), movement disorders (Takahashi et al, 2010), and epilepsy (Duncan, 2009;O'Brien et al, 2000;Kazemi et al, 2009), and is frequently used as a surrogate estimation of neural activity in clinical neurology and research studies of cerebral function.…”
Section: Introductionmentioning
confidence: 99%
“…O-15 PET images represent the immediate perfusion state of the brain at the time of image acquisition and are essentially limited to interictal (between seizures) studies because of the logistical challenge of injecting and immediately scanning the patient during a seizure. Cerebral blood flow is an important diagnostic metric in stroke (Liebeskind, 2009), neurodegenerative disease (Josephs et al, 2006), movement disorders (Takahashi et al, 2010), and epilepsy (Duncan, 2009;O'Brien et al, 2000;Kazemi et al, 2009), and is frequently used as a surrogate estimation of neural activity in clinical neurology and research studies of cerebral function.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, subtraction ictal SPECT techniques and statistical comparison with normal control SPECT databases have been validated by several studies, showing a rate of epileptogenic focus localization that was equivalent or superior to that seen in interictal-ictal side-by-side visual analysis (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…They recently compared SISCOM and STATISCOM images from 87 consecutive patients submitted to temporal lobectomy and showed superiority of STATISCOM for seizure localization. Furthermore, the authors confirmed an increased probability of seizure-free outcome when STATISCOM correctly localized the TLE subtype [73].…”
Section: Mrimentioning
confidence: 73%
“…All three methods showed value in predicting seizure-free outcome, however, in those cases with all three tests (27 patients), the ictal SPECT had the highest OR of 9.1 (p = 0.05). In order to take into account the normal variation between sequential SPECT scans of single individuals (i.e., ictal and interictal images) some investigators used neuroimaging postprocessing techniques with SPM (http://www.fil.ion.ucl.ac.uk/spm/) to create a statistical parametric mapping (SPM) and MRI voxel-based method to analyze ictal--interictal SPECT difference maps (statistical ictal SPECT coregistered to MRI (STATISCOM)) [73]. They recently compared SISCOM and STATISCOM images from 87 consecutive patients submitted to temporal lobectomy and showed superiority of STATISCOM for seizure localization.…”
Section: Mrimentioning
confidence: 99%